THE EFFECT OF PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION: A STUDY OF OVO USERS IN BANDUNG, INDONESIA - Alif Fajar Suhendar; Hariyadi Triwahyu Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The results of a survey by Insight Asia (2023) on digital wallets in Indonesia in 2023 reported that as many as 71% of respondents are actively using digital wallets. GoPay is the highest digital wallet ever used by respondents at 71% with a loyalty rate of 58% in the last three months, while the second place is OVO at 70% with a loyalty level in the last three months of 53%. The data shows that the percentage of OVO user loyalty is lower compared to GoPay users. The purpose of this study is to examine the effect of perceived ease of use and perceived usefulness on customer loyalty mediated by OVO customer satisfaction in the city of Bandung. By using a quantitative approach with data obtained through a questionnaire to 120 ovo users in the city of Bandung who were selected using the convenience sampling technique. The research variables include perceived ease of use and perceived usefulness as independent variables, and customer loyalty as dependent variables and customer satisfaction as mediating variables. The data was analyzed using SPSS Statistic 27. Research shows that perceived ease of use and perceived usefulness have an effect on customer loyalty. However, only perceived ease of use has an effect on customer satisfaction, while customer satisfaction does not show a significant influence as a mediator. This research recommends to the application manager to continue to improve the quality of service so that consumers are satisfied and loyal.